Pembrolizumab‐induced interstitial lung disease following thoracic surgery in a patient with non‐small cell lung cancer. Issue 11 (11th September 2019) - Fujita, Tetsuo; Hayama, Nami; Kuroki, Tsuguko; Shiraishi, Yuka; Amano, Hiroyuki; Nakamura, Makoto; Hirano, Satoshi; Aramaki, Nao; Ichinose, Shuji; Shimizu, Shinichiro; Tabeta, Hiroshi; Nakamura, Sukeyuki
Abstract : The safety of treatment with immune‐checkpoint inhibitors prior to thoracic surgery in patients with non‐small cell lung cancer (NSCLC) remains unclear. Here, we describe the case of a 62‐year‐old woman with NSCLC with programmed death ligand 1 expression on 85% of tumor cells. The patient was initially considered to have unresectable stage IIIB disease and received pembrolizumab monotherapy. After 12 cycles of pembrolizumab, the primary tumor was reduced, but a small lung nodule in another lobe was unchanged. Based on the course of image findings, the nodule was considered to be an old inflammatory change. The clinical stage was changed to stage IB and partial resection was performed. Three days after thoracic surgery, the patient began to complain of coughing and shortness of breath. A CT of the chest revealed ground‐glass opacity in the bilateral lung fields, suggesting interstitial lung disease (ILD) associated with pembrolizumab. Corticosteroid therapy was started and a chest X‐ray showed a reduction in the opacity with improved oxygenation. This is the first case of immune‐checkpoint inhibitor‐related ILD triggered by thoracic surgery following long‐term immune‐checkpoint therapy.